The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s13197-012-0713-0
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of canthaxanthin produced by Dietzia natronolimnaea HS-1 with spray drying microencapsulation

Abstract: The strain bacterium Dietzia natronolimnaea has propounded as a source for biological production of canthaxanthin. Because of sensitivity of this pigment, examine on its stability is important. In this study, stability of encapsulated canthaxanthin from D. natronolimnaea HS-1 using soluble soybean polysaccharide (SSPS), gum acacia (GA), and maltodextrin (MD) as wall materials was investigated at 4, 25, and 45°C in light and dark conditions during 4 months of storage. It was shown that the type of walls influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Previous study on three varieties of the Iranian palm including Deiri, Khazravi and Samaran, indicated the oil yields as 9.32, 8.54 and 10.84 respectively 1 . In another study on 14 varieties, the oil yields were given 5-9% (14).…”
Section: Seeds and Seed Oils Yieldsmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous study on three varieties of the Iranian palm including Deiri, Khazravi and Samaran, indicated the oil yields as 9.32, 8.54 and 10.84 respectively 1 . In another study on 14 varieties, the oil yields were given 5-9% (14).…”
Section: Seeds and Seed Oils Yieldsmentioning
confidence: 94%
“…1984 its constituents in chemical, cosmetics, pharmaceuticals, feed and food industries 1,2,[4][5][6][7] . In some countries such as Iran, the wastage of date seeds is a problem in agricultural and industrial processing in which they discarded or utilized on a small scale as animal feed 1,2 . So, finding a way to make a profit on the pits would benefit date farmers substantially.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
See 3 more Smart Citations